Mapping brain neural networks in stress brain connectivity - Wadan, Al-Hassan Soliman; Ahmed, Mohamed Abdelsattar; Moradikor, Nasrollah (Progress in brain research, 2025)
Stress can cause severe damage to the CNS and contribute to an increased risk of neurological and psychiatric disorders. Gaining more insight into the neurobiology of stress is essential to treating neurological disorders associated with stress, which account for a high percentage of the world’s disease burden. However, because of complicated variations in stressor types, stress perception, and preceding exposure to stressors, studying the impacts of stress is challenging. Gender, age, and timing are other crucial variables that can influence the stress response. Behavioral, physiological, genetic, and cellular/molecular neuroscience methodologies have all been widely applied in various research contexts to examine the neurobiological impacts of stress. Furthermore, because these approaches are invasive and hence undesirable or impractical for use in humans, they are frequently challenging to adapt to a therapeutic context. As an alternative to invasive procedures, functional neuroimaging approaches are starting to be developed. We discuss in this chapter brain neural networks under stress brain connection.